lama Kebuntingan, Litter size dan Bobot Lahir Kambing Boerawa pada pemeliharaan Pedesaan di Kecamatan Gisting Kabupaten Tanggamus - Adhianto, Kusuma (UPPM Politeknik Negeri lampung, 2012)
An experiment was conducted on 100 heads of Boerawa Doe mated with Male Boer. The parameters perceived were pregnancy period, litter size, and birth weight. The study was undertaken at Boerawa Goat Development Area Kecamatan Gisting, Kabupaten Tanggamus. The data were analysed in SPSS was 10. The results showed that pregnancy periode 159,31 ± 3,47 days, litter size 1,62 ± 0,65 heads and birth weight 3,02 ± 0,29 kg